The Effects of Addition of Asphaltite on the Mechanical Properties of Bitumen and Bituminous Hot Mixes - Kok, Baha Vural; Yilmaz, Mehmet; Kuloglu, Necati (Turkish Chamber Civil Engineers, 2012)
In this research the asphaltite obtained from Sirnak (Silopi) region was added to B160/220 bitumen by 2%, 4%, 6% and 8% by weight. The mechanical properties of original bitumen and asphaltite added (modified) bitumen were investigated. It was observed that standard penetration was reduced, viscosity and complex modulus were increased and there was no noticeable change on softening point and on phase angle by the addition of asphaltite. The test results on the Marshall specimens showed that retained Marshall stability, indirect tensile strength ratio, stiffness modulus at temperatures of 15 degrees C, 25 degrees C and 35 degrees C and fatigue life were significantly increased by the addition of asphaltite to bitumen. In conclusion, it is seen that the addition of certain amounts of asphaltite to bitumen can effectively improve the mechanical properties and moisture resistance of hot bituminous mixes. It was determined that 4% asphaltite content is optimum for the mixtures tested.
Asfaltitin bi?m ve bitümlü sicak karişimlarin mekanik özelliklerine etkisi
Keywords: Asphaltite; modified bitumen; modified bituminous hot mix; mechanical properties